1999
DOI: 10.1111/j.1745-9125.1999.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐oriented Policing in Violent Crime Places: A Randomized Controlled Experiment*

Abstract: Over the past decade, problem-oriented policing has become a central strategy for policing. In a number of studies, problem-oriented policing has been found to be effective in reducing crime and disorder. However, very little is known about the value of problem-oriented interventions in controlling violent street crime. The National Academy of Sciences' Panel on the Understanding and Control of Violent Behavior suggests that sustained research on problem-oriented policing initiatives that modify places, routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
399
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(412 citation statements)
references
References 43 publications
8
399
0
5
Order By: Relevance
“…Examples of successful initiatives are found in Sparrow, Moore, and Kennedy (1990); Kelling and Coles (1996);and Braga et al (1999).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of successful initiatives are found in Sparrow, Moore, and Kennedy (1990); Kelling and Coles (1996);and Braga et al (1999).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated randomized trials show that targeted increases in police patrol deployment reduce recorded crime in the targeted areas, compared to control areas, both patrolling in marked police cars (Sherman and Weisburd 1995;Telep et al 2012) and on foot (Ratcliffe et al 2011). Systematic reviews of the evidence on hot spots policing experiments suggest that the benefits associated with it exceed the costs (Braga et al 1999(Braga et al , 2012, without much evidence of spatial displacement to adjacent areas in the vicinity of the targeted hot spots (Bowers et al 2011;Weisburd et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yet others have begun to look more closely at precisely what specific aspects of police presence may more effectively prevent crime than others. For example, some have looked at problem-oriented policing (e.g., Braga and Bond 2008;Braga et al 1999;Taylor et al 2010;Weisburd and Green 1995), drug enforcement operations (e.g., Weisburd andGreen 1994, 1995), increased gun searches and seizures (e.g., Sherman and Rogan 1995a, b), foot patrols (e.g., Ratcliffe et al 2011), crackdowns (Sherman and Rogan 1995a), Bzero-tolerancep olicing or Bbroken windows tactics^ (Caeti 1999;Weisburd et al 2011), and intensified engagement (Rosenfeld et al 2014). Yet few of these studies provide detailed measures of exactly what police were doing in the experimental hot spots; even one that did (Sherman and Rogan 1995a, b) failed to measure what police did in the control hot spot.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized trial in Minneapolis that increased police patrols to crime "hot spots" decreased total crime calls between 6 and 13 percent (Sherman and Weisburd, 1995). Another experiment in Jersey City, which addressed additional police support to 12 hot spots found 30 to 60 percent reductions in calls to the police (Braga et al, 1999), and an analysis of gang injunctions in Los Angeles found that they reduced crime by 5 to 10 percent (Grogger, 2002).…”
Section: A1 Fixed Effectsmentioning
confidence: 99%